الطرق غير التقليدية في تقدير مخاطر القروض البنكية Non - Conventional Ways Of Estimating Bank Loan Risk - رقايقية فاطمة الزهراء; يخلف العربي (My University, 2019)
تهدف الدراسة إلى تحديد آلية إدارة مخاطر الائتمان المصرفي، من خلال محاولة إعطاء وصف للطرق التقنية، مع إظهار الفارق في التطبيقات العملية لأهم الطرق التي تعتمد على التقنيات الإحصائية وتستخدم التنبؤ بالحدود الافتراضية المعلمية كالتحليل التمييزي والتحليل اللوجيستي مع طرق أخرى غير معلمية كالأنظمة الخبيرة والشبكات العصبية، وكانت أهم نتائج الدراسة أن الطرق الغير معلمية لها قدرة تصنيفية أفضل من الطرق المعلمية وذلك لما حققته من معدلات تصنيف عالية الدقة وأكثر مرونة في التعامل بها كأدوات مساعدة لطريقة التحليل المالي في اتخاذ قرار منح القرض من عدمه. This study aimed at how to manage and control the credit risks of banking, By trying to describe the technical methods, while showing the difference in the practical applications of the most important methods that rely on statistical techniques and used prediction such as discriminatory analysis and logistic analysis with other methods non-parameter , such as expert systems and neural networks, the most important results of the study was that non-parameter methods have a better taxonomic ability than Parametric methods, Because they have achieved high ratings and are more flexible in dealing with them, as tools to assist the method of financial analysis in deciding whether to grant loans.